An empirical analysis on how relevance and credibility of content affect consumer brand engagement in Facebook and Instagram in a mixed business model - Moisio, Etleva (2020)
The expansion of social media as marketing channel is explained by its efficiency in reaching multitudes in a short time at low costs. The new marketing channels require new marketing approaches aiming to achieve new marketing goals. Content marketing as an efficient marketing approach has received great interest from both academics and practitioners especially for its ability to drive consumer brand engagement (CBE) as the new desirable outcome of brand’s efforts in social media. Relevance, an intuitively understood concept, is considered a must for content to drive consumer brand engagement. On the other hand, credibility as a subjectively perceived concept is an important criterion that consumers apply when deciding on what content they want to engage with. Despite their importance, not much has been done to empirically assess the effect of content relevance and content credibility on CBE and the role of content credibility on CBE in a social media environment, more specifically on Facebook and Instagram. While consumer engagement in B2C and B2B business model contexts has received increased attention, the same thing cannot be said for the mixed business model context that this study applies. The purpose of this study is to empirically assess the impact on CBE that relevance and credibility of content created by a mixed business model company and distributed on its Facebook and Instagram global profiles. CBE as a multidimensional concept is measured through three dimensions of cognitive processing, affection and activation based on Hollebeek, Glynn and Brodie (2014) conceptualization and scale. The direct effect of content relevance and content credibility on brand trust (BT) was assessed based on previous literature. This study also evaluates the effect of CBE on BT and word of mouth intentions (WoM) as the desired outcomes of CBE. Based on previous studies the effect of BT on WoM was assessed. Quantitative approach is found appropriate for this study. As result of an online survey, 426 valid responses were received (N= 426). SPSS and SmartPLS 3.0 were used to analyze the collected data. Based on results, content relevance and content credibility show significant positive effect on each of the three dimensions of CBE. Content credibility also shows significant direct effect on BT, whereas this is not the case for content relevance being the only hypothesis that is not supported in this study. As expected, CBE has significant positive effect on both BT and WoM. A strong effect of BT on WoM intentions is noticed. CBE is identified as mediator in the relationship between content relevance and BT as well as on the relationship between content credibility and BT. Brand trust is identified to be a mediator in the relationship between CBE and WoM.